Patient's satisfaction on outpatient pharmacy services in government hospitals / Faizah Abd Rahman - Abd Rahman, Faizah (2010)
Objectives: The study is to establish the level of satisfaction with OPD services, to determine the relationship between patient characteristics and satisfaction level, to study the extent of correlations between dimensions and to identify the gap between Ministry of Health (MOH) and Marquez-Peiro, 2008 Questionnaire. Methodology: A cross - sectional survey was carried out among patients who visited two OPD in two government hospitals. Data were collected using structured and validated questionnaire consisting of 8 questions related to patient characteristics and 6 dimensions with 24 questions related to patient satisfaction. Descriptive statistics, Parametric and Nonparametric such as independent sample t-tests, Kruskal Wallis Test, Mann-Whitney U Test were used for data analysis. Pearson correlation Test also used to identify the correlations between dimensions. Results: A total of 309 out of 350 questionnaires distributed were completed and collected. The respondents comprised 53.1% male and 46.9% female. All dimensions were identified as not different significantly in both hospitals. Further analysis on each questionnaire observed the 3 most influential variables affecting patient's satisfaction are waiting time, waiting area and pharmacists' assessment on patient medication. It was found that overall Patient Satisfaction Index (PSI) for both hospitals is 70.38%. The strongest correlation was found between D4 and D5 and the weakest correlation between Dl and successfully identified. Conclusions: The study concluded that different hospitals have different outcomes on patient's satisfaction level. This is due to the differences in patients' characteristic, layout of the OPD area, systems workflow and pharmacist skills and experiences.